HUBUNGAN DAYA TERIMA MAKANAN TERHADAP ASUPAN ENERGI DAN PROTEIN PADA SISWA DI ASRAMA MAN MODEL SINGKAWANG - Nurlina Nurlina; Widyana Lakshmi Puspita (Pontianak Nutrition Journal (PNJ), 2018)
Implementation of the food is a series of activities that constitute a system includes activities or sub-system of budgeting food, planning menus, making estimates of foodstuffs, provision or purchase groceries, reception, storage and distribution of food ingredients, preparation and cooking of food, assessment and distribution food, recording and reporting and evaluation carried out in the framework of the provision of food for the population in the institution. This study aims to determine the relationship of the acceptability of food energy and protein intake in students in the dormitory MAN Model Singkawang. This type of research is observational with cross sectional approach. Sampling using simple random sampling technique to obtain a sample of 48 students. Primary data collected included the acceptability of food, intake of energy and protein intake. While the secondary data includes a general overview of the research and the number of students that will be investigated. The analysis used include univariate and bivariate analysis using chi square test. Based on statistical analysis using chi square test, shows that there is a relationship between the received power of food to energy and protein intake in students in a dormitory MAN Model Singkawang (p <0.05).